Particularities of clinical - laboratory and instrumental markers of the digestive system comorbid pathology in HIV-infected patients in the context of family medicine practice - Vysotskyi Володимир (Psychosomatic Medicine and General Practice, 2020)
Introduction. Ukraine remains in second place among the largest countries with HIV - epidemic in Eastern Europe and Central Asia, with one of the highest infection rates among European region’s countries. The issues of comorbidity of various pathologies, including HIV - infection with digestive system diseases, and the increasing role of family medicine in the detection and treatment of many chronic gastroenterological diseases in HIV-infected patients become actual in Ukraine. Purpose of the study. To study the characteristics of clinical, laboratory and instrumental markers of the digestive system comorbid pathology in HIV-infected patients in the context of clinical diagnostic value for the family medicine practice. Material and methods. The 96 patients with HIV infection, who were monitored in HIV / AIDS centers in different regions of Ukraine during 2017-2019 years were examined: the main group (MG) of the study was 54 (56.2%) HIV-infected patients with digestive system pathology and the control group (CG) - 42 (43.8%) HIV-infected patients, who did not have a comorbid pathology of the digestive system. The examination included general clinical, biochemical, serological, molecular genetic studies, ultrasound of the abdominal organs in 2D scanning mode in two projections. Results and its discussion. In both groups, astheno-vegetative and dyspeptic syndromes were observed, but their manifestations in the MG appeared significantly more often (p <0.05), than in the CG and were more expressed. Among laboratory parameters in patients with comorbid pathology, anemia and thrombocytopenia were more often found, and the incidence of leukopenia increased with increasing immunodeficiency and had an inverse correlation with the number of CD4+ T cells. Among MG patients in comparison with CG the frequency of increased transaminase activity was higher, which may be due to the high frequency of liver damage in this group of patients. The highest activity of liver enzymes was determined in patients with comorbid pathology and severe immunodeficiency. According to the ultrasound results in MG patients the hepato- and splenomegaly, signs of portal hypertension, changes in the pancreas were more often detected and more significant. Conclusion. In HIV-infected patients with pathology of the digestive system, manifestations of astheno-vegetative and dyspeptic syndromes, changes in general clinical, biochemical and ultrasound markers were significantly more often observed and more expressed. These markers of comorbid pathology of the digestive system in HIV-infected patients are available for monitoring and control in current practice of primary care clinics for timely diagnosis and effective treatment of digestive system pathology in HIV-infected patients by family physicians.